PENERAPAN INKUIRI TERBIMBING DIPADU BRAINSTORMING ACTIVITIES UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS TERPADU PADA PEMBELAJARAN BIOLOGI SISWA KELAS XI MIA 2 SMA N 1 KARANGANYAR - Amalia Rosyada; Murni Ramli; Dewi Puspita Sari (BIO-PEDAGOGI, 2015)
The research objective was to improve student’s Intergated Science Process Skill (SPS) on biology by guided inquiry learning combined with brainstorming activities of XI MIA 2 SMA N 1 Karanganyar. The research was Classroom Action Research with 2 cycles which consisted of 4 phases namely planning, action, observation, and reflection. Intergated Science Process Skill was assessed in this research were constructing hypothesis, designing investigation, investigation, collecting and processing data was assessed by observation and integrated SPS cognitive test. The subject of the research was 36 students of XI MIA 2 SMA Negeri 1 Karanganyar academic year 2014/2015. The data were analyzed using qualitative descriptive technique. The result in cycles I and II showed that Intergated SPS on biology significantly increased by the guided inquiry learning model combined with brainstorming activities. The improvement based on observation results in constructing hyphothesis was about 62,8%, designing investigation was about 72,69%, investigation was about 79,63%, and collecting and processing data was about 68,98%. The improvement based on Integrated SPS cognitive test results in constructing hyphothesis was about 91,67%, designing investigation was about 82,41%, collecting and processing data was about 65,97%. The research concluded Integrated SPS was significantly increased guided inquiry model combined with brainstorming activities at grade XI MIA 2 in SMA Negeri 1 Karanganyar Keywords: guided inquiry learning model, integrated science process skill, brainstorming activities